PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWAPADA MATA PELAJARAN MATEMATIKA MELALUI PENERAPANTEORI BELAJAR GAGNE - dan Resti Anggraeni, Farah Nirmala, Maryati, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research is aimed at improving the motivation and learning achievementin mathematics among the grade 5 students of Panjangrejo I State Elementary Schoolthrough the application of Gagne’s learning theory.This study is a classroom action research. The subjects are the grade 5 students ofPanjangrejo I State Elementary School, 16 male students and 12 female students. Theresearch method is test and non test in the forms of observation, questionaire, interview,and field notes. The instruments of data collection are test items, observation sheets,questionaire sheets, interview guides, and field notes. The data analysis supported bythe quantitative is descriptive qualitative. This research was conducted in three cycles.The research was stopped when the students reached the minimal score of 65.The result of the research shows that the students’ learning motivation is high(39,29% in cycle I, 64,29% in cycle II, and 89,29% in cycle III). It means it improves 25%from cycle I to cycle II and also 25% from cycle II to cycle III. The learning achievementin the cognitive (c) and psychomotoric (p) aspects in cycles I, II, dan III reaching theminimal score is 32,14% (c) and 75% (p), 78,57% (c) and 96,43% (p), 100% (c) and 100%(p). It means the learning achievement in mathematics improves from cycle I to the endof cycle III. In other words, Gagne’s learning theory implemented in grade V of Panjangrejo1 state elementary school can improve the students’ learning motivation and learningachievement.Key words: learning motivation, learning achievement, mathematics, Gagne’s learningtheory